ANALISIS TITIK IMPAS DAN KELAYAKAN FINANSIAL USAHATANI BAWANG MERAH SKALA ULTRA KECIL DI DATARAN TINGGI BENGKULU - Deka Saskia Ananta; Novitri Kurniati; Edi Efrita; Elni Mutmainnah (BUANA SAINS, 2025)
Shallot farming on marginal land with an ultra-small scale (0.1 ha) faces different efficiency and profitability challenges compared to larger-scale farming. This study aims to analyze the cost structure, income, financial feasibility, and break-even point of ultra-small-scale shallot farming in Air Duku Village, Rejang Lebong Regency. Using a quantitative descriptive method with a case study approach, this research involved 12 farmers selected through purposive sampling based on the criteria of actively cultivating shallots for at least two growing seasons on 0.02-0.08 ha of land. Data were collected through structured interviews and analyzed using income analysis, R/C ratio, and Break-Even Point (BEP) analysis. The results showed that the average production cost was IDR 4,479,187.48 per growing season, with a net income of IDR 5,920,812.52. An R/C ratio of 1.32 indicates that this farming practice is financially feasible and profitable. The production break-even point was achieved at 172.28 kg, far below the actual production (400 kg). Similarly, the sales break-even point (IDR 4,479,187.48) was below the actual revenue (IDR 10,400,000). These findings confirm that ultra-small-scale shallot farming still has promising economic prospects and a low risk of loss, although there is room for improvement in input use efficiency, particularly in terms of seed and labor utilization. The policy implication of this research is the need for technical assistance to optimize the productivity of smallholdings and improve farmer access to more efficient production inputs